Ion exchange membrane
By using thin films containing amyloid fibers in fuel cells, the existing proton exchange membranes are solved, and the membrane performance with high conductivity and mechanical strength is achieved, which is suitable for low temperature and low humidity conditions.
Patent Information
- Application Number
- CN202080054729.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-30
- Filing Date
- 2020-07-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2040-07-29
AI Technical Summary
Existing proton exchange membrane fuel cells are costly and non-biodegradable, especially under low humidity and low temperature conditions.
A thin film containing amyloid fibers is used as an ion exchange membrane, and a film with high conductivity and mechanical strength is formed by a combination of an aqueous liquid and a protein solution.
A low-cost, biodegradable proton exchange membrane is achieved, with similar properties to traditional NafionTM membranes, and has good moderate performance under low temperature and low humidity conditions.
Smart Images

Figure CN114175326B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the use of organic molecules, such as proteins, in the form of amyloid fibrils in ion exchange membranes which can be used in electrochemical devices, such as fuel cells. Prior art
[0002] A fuel cell (FC) is a cell in which voltage is generated by the oxidation of a reduced fuel (e.g. hydrogen: H2) at the anode (electron emitter) coupled with the reduction of an oxidant, such as oxygen (O2) from the air, at the cathode (electron collector). Proton exchange membrane fuel cells, also known as polymer electrolyte membrane fuel cells (or PEMFCs), are a type of fuel cell developed for applications in the field of transport (cars, buses, airplanes, etc.) as well as in laptops and mobile phones. Their specific characteristics include operation in a low pressure range (typically atmospheric pressure to 10 bar) and temperature (typically 20-100 °C) and a specific electrolyte membrane.
[0003] For the battery to work, the membrane must be able to conduct hydroxide ions (H3O + ), also denoted as H in a simplified version + , but cannot conduct electrons. The membrane must also meet a number of additional criteria to be effective. First, it must not allow any gas to flow from one side of the cell to the other. This phenomenon is known as "gas crossover". The membrane must resist the reducing environment of the anode and, at the same time, the oxidizing environment of the cathode. It must also be able to operate over the widest possible operating humidity and temperature range of the PEMFC. Finally, an important source of energy losses is the membrane's resistance to the flow of protons. This resistance is minimized by making the membrane as thin as possible (approximately 50-20μm). Sulfonated polystyrene membranes were originally used for electrolytes, but were replaced by the ionic polymer Nafion in 1966. TM Instead, the ionic polymers excel in performance and durability. Polymers comprising heterocyclic units based on poly(pyrrole) and comprising proton acceptor and donor groups are described in WO2009 / 040362 as being able to form such membranes. To date, the perfluoropolymer Nafion produced by Dupont TM It is still the reference material for the manufacture of proton exchange membranes. However, other industrial groups (Aciplex, Flemion, 3M, SCC) have developed alternatives (see Kusoglu & A.Z. Weber, Chemical Reviews 117, 987-1104 (2017) [1]).
[0004] The operation of hydrogen-oxygen cells is particularly clean, as they only produce water and heat and consume only gases. Therefore, they are considered to have very low environmental impact. However, the cost of ion exchange membranes, and especially proton (H3O+ The cost of ions is still the main limiting factor in the development of PEMFC-type FC. Another problem comes from the composition of membranes such as Nafion TM The inertness of the perfluorinated material is that it is not biodegradable. Finally, another problem lies in the moderate performance at low humidity (less than 50%) and low temperature (less than 50°C).
[0005] Therefore, there is a need for low-cost and / or biodegradable ion exchange membranes that also exhibit one or more of the above-mentioned properties that are unique to such membranes and similar to Nafion TM Therefore, the object of the present invention is to remedy this need. Summary of the invention
[0006] Surprisingly, the Applicant has established that organic materials, and in particular biomaterials, comprising amyloid-type fibrils are able to fully or partially meet these very specific needs.
[0007] Amyloid fibers are very stable fibrous nanostructures formed by the spontaneous self-assembly mechanism of proteins or polypeptides. These fibers have the same type of intermolecular β-sheet structure. Amyloid acquires a secondary structure rich in β chains, which are bound via H bonds to form these β-sheets. The formation of these β-sheets and fibers spontaneously depends on external parameters, in particular the pH and ionic strength of the medium, the concentration of proteins or polypeptides, the presence of other molecules or further temperature and stirring parameters, which can lead to different fibrillation dynamics and organizations. Functionalized amyloid fibers can be used as electronically conductive nanowires (see WO2012 / 120013). Hydrogels containing α-lactalbumin are considered to be potentially useful in the biomedical field (dressings) or coatings (see WO2012 / 136909).
[0008] In the field of batteries, it is also generally known to use enzyme proteins to catalyze oxidation and / or reduction reactions at the anode or cathode. PCT application WO2008058165 describes such a battery. For its part, PCT application WO2009040362 describes a fuel cell proton exchange membrane as a known proton exchange membrane such as Nafion TM These alternative membranes include grafted polymers containing a main chain with heterocyclic units, such as polypyrroles with side chains or "grafts". These grafts can contain peptides or polypeptides of 1 to 10 polypeptide units. These molecules are clearly not amyloid fibers.
[0009] The subject of the present invention is an ion exchange membrane, in particular a proton, comprising an aqueous liquid and a membrane comprising amyloid fibers.
[0010] A thin film is a structure whose lateral dimensions greatly exceed its thickness. "Greatly exceed" is generally understood to mean that the lateral dimensions are at least 100 times the thickness. The thickness can advantageously be selected in the range from 10 nm to 1 mm, preferably 100 nm to 150 μm, in order to prevent gas crossover while not substantially restricting conduction. A thickness in the range of 1 to 75 μm, in particular 15 to 55 μm (e.g. 20 to 30 μm), allows particularly satisfactory results to be obtained. The surface of the film can then be 1 mm thick. 2 Up to 10cm 2 Select from the range, preferably 1 to 50 mm 2 A membrane is a thin film with a structure through which transfer can occur under various driving forces.
[0011] Another subject of the invention is a film comprising or consisting of amyloid fibers.
[0012] The membrane according to the invention comprises such a film, which itself preferably comprises amyloid fibers in a network or consists of amyloid fibers. It will be recalled that amyloid fibers are generally fibers produced by the self-assembly of proteins or polypeptides. This self-assembly has the characteristics of self-propagation, because the addition of a small amount of protein in the form of amyloid fibers (seeding process) to a suspension of the same protein accelerates the growth kinetics of the amyloid fibers. Amyloid fibers exhibit a characteristic intermolecular β-sheet structure and also have a characteristic X-ray diffraction pattern. Therefore, amyloid fibers correspond to the stacking of polypeptides / proteins in linear and usually non-branched fibers. These fibers are stabilized by stacking of β-chains arranged perpendicular to the fiber axis and connected by a hydrogen bond network. They typically show Congo red staining associated with birefringence under polarized light (Sipe & Cohen, Journal of Structural Biology 130, 88–98 (2000) [2]) and result in a sharp increase in fluorescence emitted by thioflavin-T at a wavelength of 480 nm (Sabaté et al., Journal of Structural Biology 162, 387-396 (2008) [3]). Amyloid fibrils are typically characterized by a high shape factor (“aspect ratio”): when the fibrils form spontaneously, the diameter ranges from a few nanometers to tens of nanometers for lengths of the order of one to ten micrometers (Doussineau et al., Angewandte Chemie International Edition 55, 2340-2344 (2016) [4]).
[0013] In the context of the present invention, "amyloid fibers" therefore refer to fibers comprising or essentially consisting of at least one polypeptide or at least one protein, the fibers comprising stacks of β-chains of the proteins or polypeptides, the chains arranged perpendicular to the fiber axis being connected by a network of hydrogen bonds. Advantageously, there are one or more additional structural features mentioned, such as their size and / or their aspect ratio. The amyloid fibers used in the context of the present invention can be from any source, natural or synthetic. Preferably, they comprise or consist of at least one peptide or protein, and are preferably biologically based or biologically derived, such as α-lactalbumin, lysozyme, β-lactoglobulin, the prion domain of Het-s and insulin. It is also contemplated to use a mixture of fibers from different sources, although the use of a single type of fiber has the advantage of simplicity. Advantageously, they are selected from a group of molecules that are cheap and / or available in large quantities, such as α-lactalbumin or lysozyme. A single protein or protein mixture can be used to implement the present invention. Amyloid fibers can also come from polypeptides, or even from peptides.
[0014] According to a preferred aspect of the invention, the film and / or membrane according to the invention is made from a protein solution which subsequently forms a hydrogel in an aqueous medium. After deposition and drying of the hydrogel, a film is then obtained whose matrix comprises a fibrous network which comprises or consists essentially of amyloid fibers.
[0015] Of course, the aqueous liquid allowing the preparation of the hydrogel or present in the film essentially comprises water, but may contain other compounds in small proportions, such as salts or other additives in solution. The expression "small proportion" may mean that the liquid consists of at least 80% of water by mass relative to the total mass of the liquid, preferably at least 90% of water by mass relative to the total mass of the liquid, in particular at least 95% of water by mass relative to the total mass of the liquid. Such hydrogels are generally referred to as supramolecular gels.
[0016] The film and / or membrane may advantageously be formed by depositing a protein solution, the concentration of which is generally between 1 g / L and 500 g / L. Preferably, the concentration of the solution is generally between 1 g / L and 150 g / L or in the range of 1 g / L to 150 g / L (that is, between 0.1% and 15% or in the range of 0.1% to 15% by mass relative to the aqueous solvent). The concentration of the protein solution may advantageously be in the range of 25 g / L to 100 g / L.
[0017] It is also preferred that the film and / or membrane according to the invention is self-supporting (or is self-supported), that is to say, has sufficient rigidity to be able to be handled and placed in a device, such as a battery according to the invention. However, according to a variant of the invention, the film and / or membrane may also contain mechanical reinforcements and / or one or more additives. These additives may have one or more purposes and are in particular selected from:
[0018] - ions that regulate ionic conduction,
[0019] - plasticizers that adjust the level of mechanical properties (Young's modulus E [MPa], reduction of the glass transition) and facilitate the implementation of the membrane, for example polymers such as methylcellulose, organic and inorganic derivatives with a silica base,
[0020] - a cross-linking agent, such as glutaraldehyde (pentanedial-1,5-dialdehyde), to (irreversibly) chemically cross-link the membrane in order to ensure chemical and dimensional stability,
[0021] - antioxidants and free radical traps to limit chemical degradation processes of the membrane, such as natural antioxidants (e.g. vitamin E (in its 8 natural forms: α-tocopherol, β-tocopherol, γ-tocopherol, δ-tocopherol, α-tocotrienol, β-tocotrienol, γ-tocotrienol and δ-tocotrienol, ascorbic acid, 3,4-dihydroxycinnamic acid) or metal cations such as cerium,
[0022] -UV stabilizers to limit any light degradation.
[0023] Preferably, the method for making the film and / or membrane may include a chemical cross-linking step. The cross-linking agent may, for example, be a compound such as glutaraldehyde. The cross-linking step may be performed by adding a cross-linking agent to the already formed film and / or membrane, for example by exposing the film or membrane to cross-linking agent vapor.
[0024] Advantageously, the membrane according to the invention does not allow the passage of electrons. It is also preferred that it does not allow the passage of gases. Advantageously, the membrane should be resistant to reducing environments (such as hydrogen-rich media) and at the same time resistant to oxidizing environments, such as air (oxygen). Finally, it is also preferred that the membrane may have the ability to exchange ions.
[0025] - at low temperature, for example 0°C to 45°C, preferably 10°C to 30°C, and especially 25°C; and / or
[0026] - at low relative humidity, for example 45% to 75%, preferably 55% to 65%, in particular about 60%.
[0027] Preferably, it should also be capable of operating at the most common operating temperatures of PEMFCs (45°C to 95°C) and at relative humidity of 60% to 100%, the humidity level being determined in the usual manner.
[0028] The membrane allows ion exchange, and in particular proton exchange. However, other ions, cations or anions, in particular hydroxide ions OH can be exchanged. - .
[0029] Another object of the invention is a battery, preferably a fuel cell, comprising:
[0030] -anode;
[0031] - cathode; and
[0032] - a membrane located between the anode and the cathode,
[0033] The membrane comprises an aqueous liquid and a thin film comprising amyloid fibers.
[0034] Preferably, the membrane comprises or consists of a membrane such as described in the present application. The membrane in the battery according to the invention acts as an electrolyte, since it contains ions that can permeate by diffusion and circulate in the film matrix. The membrane together with the anode and cathode constitutes the heart of the battery.
[0035] It is also preferred that the membrane comprising amyloid fibers is as described in this application.The basic device according to the invention comprising an anode, a cathode and a membrane can be described as an electrochemical cell, or simply a cell.
[0036] The anode and cathode can be of any type, but are usually selected from standard types made of materials that allow electrochemical reactions to take place at the anode and cathode. In the case of PEMFC, they are usually composed of an ionic polymer and a catalyst of a conductive material such as a fabric or carbon powder, for example, 2 to 4 nm platinum particles. These materials are usually associated with a gas diffusion layer (GDL). This layer can ensure the uniform distribution of the gas, the possible good management of the water in the cell, and the mechanical strength of the membrane and the active layer containing the reactive materials of the anode and cathode. Such a layer usually consists of a porous carbon fabric that can be between 100 μm and 300 μm thick and coated with a polymer, usually PTFE. The carbon fibers of the fabric can be arranged in different ways, such as woven and non-woven.
[0037] The cell according to the invention may also comprise additional elements, in particular when the cell according to the invention is a fuel cell (FC), in particular of the proton exchange membrane fuel cell (PEMFC) type.
[0038] Therefore, according to a preferred aspect, the battery according to the invention further comprises two plates:
[0039] - a first plate for distributing a reducing fuel, such as hydrogen, and
[0040] - A second plate for distributing the oxidant and possibly for draining the water.
[0041] Each of these plates may be made of or comprise machined graphite, metallic materials and / or carbon / polymer or carbon / carbon composite materials. In addition to their distribution function, the plates may also ensure the seal between the anode and cathode chambers, possibly manage the water produced at the cathode, collect the electrons produced at the anode and redistributed at the cathode, to maintain the battery within its operating temperature range by means of an integrated cooling system and / or ensure the mechanical cohesion of the battery pack during clamping and operation.
[0042] Another element of the battery according to the invention is the possible presence of sealing means, in particular seals. These have the function of ensuring the sealing of the battery cells necessary for optimal and safe operation of the battery and can be made of PTFE, silicone and EPDM (ethylene propylene diene monomer).
[0043] Another object of the present invention is also to stack battery cells to form a FC according to the present invention as described above. A plurality of battery cells are combined in series to form a stack in order to generate sufficient power for a specific desired application. In this case, the plates are bipolar plates, which allow such stacking.
[0044] Another object of the invention is the use of the material based on amyloid fibers in the manufacture of batteries with single cells, batteries using stacks of battery cells and preferably FC. These batteries are in particular the batteries described in the present application. Advantageously, the material based on amyloid fibers is a film consisting of a fiber network of proteins, in particular as described in the present application. The preferred use according to the invention is the manufacture of membranes for batteries, in particular for FC. In particular, these batteries are batteries according to the invention.
[0045] Another object of the invention is a method for manufacturing a film or membrane according to the invention, characterized in that a gel of amyloid fibers is formed and then spread and dried to form the film or membrane. Preferably, the gel is formed by contacting one or more proteins with water under acidic conditions, such as pH 2 to 3, or neutral conditions (such as pH 7 when the protein is insulin) and possibly slightly heated (temperature below 80°C).
[0046] Another object of the invention is a device comprising a membrane and / or a cell according to the invention and described in this application.
[0047] Another object of the invention is to use the battery according to the invention for the manufacture of emergency power supply equipment, portable technology (computers, mobile phones, chargers, etc.) or equipment requiring a power requirement of less than 100 kW.
[0048] Another object of the invention is an electrical device comprising a battery or a battery stack according to the invention, such as those described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] The invention will be better understood from a reading of the following description given by way of example only and with reference to the accompanying drawings, in which:
[0050] [ Figure 1 ] Figure 1 is a schematic diagram and partial representation of PEMFC type cells of Example 3 (Example according to the invention) and 5 (Comparative Example).
[0051] [ Figure 2 ] Figure 2 Display based on Nafion TM Polarization and power curves of conventional membrane PEMFC and α-lactalbumin (α-LAC) based membrane based PEMFC.
[0052] [ Figure 3 ] Figure 3 Polarization curves and power curves of PEMFC based on α-lactalbumin (α-LAC) membrane and PEMFC based on 95 / 5 lysozyme / methylcellulose membrane are shown. DETAILED DESCRIPTION
[0053] Example 1: Production of α-lactalbumin-based films according to the invention
[0054] α-Lactalbumin (cow source, CAS No. 9051-29-0) was obtained from DAVISCO (USA) with a purity greater than 90%. These proteins were diluted at a rate of 40 g / L in a 50 mM aqueous hydrochloric acid HCl solution to obtain a final pH value equal to 2. The suspension was incubated at 45 ° C with moderate stirring for several days (usually 3 days) until amyloid fibers were formed, which in the case of α-lactalbumin was manifested as the formation of a thixotropic hydrogel. The presence of amyloid fibers was verified by electron microscopy. 0.8 g of the solution was poured dropwise onto a PTFE-coated (Techniflon 208A, 80 μm thick, 53% PTFE by mass, 107 g / m 2 ) on a support made of glass fiber and dried in air at room temperature for 24 hours to form a self-supporting film (20 μm thick).
[0055] Example 2: Production of lysozyme-based films according to the invention
[0056] Lysozyme from hen egg white (avian origin, CAS No. 12650-88-3) was obtained from Sigma-Aldrich (reference No. L-6876) with a purity of about 95%. These proteins were diluted at a rate of 40 g / L in an aqueous solution of hydrochloric acid HCl containing 90 mM NaCl, with a final pH of 2.7. The suspension was incubated at 60° C. with moderate stirring for several days (usually 3 days) until amyloid fibers formed, which in the case of lysozyme manifested as the formation of a hydrogel. The presence of amyloid fibers was verified by electron microscopy. In this example, a 5% by mass HCl solution of methylcellulose (pH 3) was added to the lysozyme solution to improve the mechanical properties (stability, elasticity) of the film obtained after drying.
[0057] 0.8 g of the solution was poured dropwise onto a plate coated with PTFE (Techniflon 208A, 80 μm thick, 53% PTFE by mass, 107 g / m 2 ) on a support made of glass fiber and dried in air at room temperature for 24 hours to form a self-supporting film (20 μm thick).
[0058] Example 3: Production of fuel cells
[0059] Cells according to the invention were each produced with the membranes of Examples 1 and 2. For each cell, the membrane 30 was separated from its respective support and positioned between two electrodes 20 of a conventional test fuel cell (hydrogen) from the company Paxitech (France). In general, the hydrogen / air fuel cell had a 5 cm 2 active surface.
[0060] The commercial gas diffusion electrode was placed on a Sigracet 29BC brand gas diffusion layer (purchased from Fuelcellstore (USA)). It is a non-woven carbon paper treated with 5% PTFE with a microporous layer (MPL). Its total thickness is 235 μm (micrometers). The electrode thus contains 0.5 mg.cm on a Vulcan type carbon powder support deposited on a carbon fiber paper (Sigracet 29BC). -2 Platinum charge.
[0061] The electrodes themselves are positioned on an outer graphite plate 10 which is machined with a serpentine gas flow. That is, the active surface comprises serpentine grooves (not shown) of 1 mm width by 1 mm depth.
[0062] PTFE gaskets and subgaskets are used to prevent gas leakage and ensure adequate electrical insulation.
[0063] Example 4: Battery performance according to the present invention
[0064] In operation, hydrogen (H2) is passed through Figure 1 The left plate 10 enters. Once at the anode, the hydrogen dissociates (oxidizes) to H according to the following formula: + Ions and electrons: 2H 2 =4H + +4e - The ions then pass through the membrane 30, but the blocked electrons are forced into an external circuit that produces an electric current. At the cathode, the hydrogen ions, electrons, and oxygen (pure or from air) meet to form water according to the following reaction: 4H + +4e - +O2 = 2H2O. Water and oxygen pass through the right side plate 10. This reaction will also generate heat which can be recovered.
[0065] Figure 3 Shown are the polarization and power curves obtained by lysozyme- and α-lactalbumin-based membranes discharged galvanostatically for 30 s at room temperature under atmospheric pressure with humidified gas (minimum relative humidity of 60% RH) (H2 and air) at respective flow rates of 20 mL min-1.
[0066] These results show that films containing amyloid fibrils are also good proton conductors. Lysozyme-based films resulted in slightly lower performance (7 mW cm at 0.4 V) compared to α-lactalbumin. -2 ). Polarization curves and power curves of PEMFC based on α-lactalbumin (α-LAC) membrane and PEMFC based on 95 / 5 lysozyme / methylcellulose membrane. The discharge was carried out in air at 1 atm of H2 and 60% humidity level.
[0067] Comparative Example 5: Producing a Nafion TM Membrane battery
[0068] In order to demonstrate the advantages of the membrane according to the invention, a comparative test was carried out. The only difference between the devices was the use of a membrane 30 (DUPONT Nafion TM NRE212, thickness 50 μm - CAS No. 31175-20-9) replaced the film according to the invention (30). The test was carried out under the same conditions as above, except that the discharge was carried out at a humidity level of 100% instead of 60%.
[0069] Figure 2 Shown is the polarization curve (black) and power curve (blue) of a PEMFC cell based on Nafion TM Conventional membranes and α-lactalbumin (α-LAC) based PEMFCs were prepared. Discharge at 1 atm H2 and 60% α-lactalbumin and 100% Nafion TM The humidity level in the air.
[0070] The performance obtained at 25 °C (22 mW cm-2 at 0.4 V) shows that the α-LAC based membranes are excellent proton conductors and are able to approach the performance of Nafion under these conditions (25 °C, RH 60%). TM (32mW cm-2 at 0.4V) performance.
[0071] Example 6: Production of cross-linked films based on α-lactalbumin and glutaraldehyde according to the present invention
[0072] The free-standing protein film was also subjected to a chemical cross-linking step in the presence of glutaraldehyde vapor (supplier Sigma-Aldrich, 50% by mass in water).The protein film of Example 1, once dried, was subjected to glutaraldehyde vapor for 30 min at 25°C.
[0073] This crosslinking step makes the self-supporting film resistant in aqueous solutions at acidic pH (test pH=3) and up to 80°C. Thus, in PEMFC operation, this step allows the cell to operate over a wide temperature range. Its temperature resistance ranges from 35°C without chemical crosslinking to at least 60°C after chemical crosslinking, or even higher. In addition, a PEMFC comprising such a membrane does not lose its performance after operating for many days.
[0074] The present invention is not limited to the embodiments described herein, and other embodiments will become clear to those skilled in the art. In particular, it is contemplated that peptides capable of forming amyloid fibers can be used, which organize themselves into hydrogels. It is also possible to use the membrane according to the present invention in any type of PEMFC. It can be used not only in hydrogen fuel cells, but also in direct methanol fuel cells (DMFC).
Claims
1. A fuel cell, comprising: - Anode; - cathode; and - a proton exchange membrane located between the anode and the cathode, the membrane A film comprising an aqueous liquid and amyloid fibers, wherein the aqueous liquid means that the liquid includes at least 80% water by mass relative to the total mass of the liquid; the amyloid fibers refer to fibers comprising at least one polypeptide or at least one protein, wherein the fibers comprise stacks of β-chains of the protein or the polypeptide, and the chains arranged perpendicular to the fiber axis are connected by a hydrogen bond network.
2. The fuel cell according to claim 1, wherein the thickness of the film is selected from the range of 10 nm to 1 mm. 3 . The fuel cell according to claim 1 , wherein the amyloid fibers comprise at least one of α-lactalbumin or lysozyme.
4. The fuel cell according to claim 1, wherein the film further comprises an additive selected from the group consisting of ions, plasticizers, and cross-linking agents.
5. The fuel cell according to claim 1, wherein the cell further comprises two plates: - a first plate for distributing the reduction fuel, and - Second plate for distributing the oxidant. 6 . A fuel cell stack comprising at least two stacks of the fuel cells according to claim 1 . 7 . An electrical device comprising the fuel cell according to claim 1 or the fuel cell stack according to claim 6 .
Citation Information
Patent Citations
Bioanode and biocathode stack assemblies
WO2008058165A2
Proton conducting membranes for fuel cells having a proton gradient and method for preparing said membranes
WO2009040362A1
Biodegradable electroconducting nanowire, its method of manufacture and its uses
WO2012120013A1
Thixotropic ?-lactalbumin hydrogels, method for preparing same and uses thereof
WO2012136909A2
Anhydrous proton conducting type fuel cell proton exchange membrane and preparation method
CN108281691A